Cirsoid aneurysm-a rare congenital anomaly of arteriovenous malformation - Bilodi, AKS; Sudharshan, P; Srinivas, TD (Journal of Institute of Medicine Nepal, 2007)
Background: The aim of the present study is to report a case of arterio venous malformation that was observed in the scalp - Cirsoid aneurysm Case Study: A. case of cirsoid aneurysmwas seen in a male patient aged twenty two years who. came to surgical out patient department with history of headache & a single large pulsatile swelling over left fronto parietal region.. with no history of trauma or infection . Histopathological studies showed arteriovenous aneurysm. Multiple ligation with excision of sac was done. Post operative period was uneventful. This vascular malformation is rare congenital anomaly, This congenital anomaly is of profound clinical importance not only to neurosurgeons but also to vascular surgeons and gastro enterologists hence it was studied and reported. Key words: Arteriovenous aneurysm, Pulsatile swelling, Cirsoid Aneurysm, Rare congenital anomaly- Vascular Malformation. The full text of this paper is available at Journal of Institute of Medicine website